Close-up C1 - Healan, Angela (HEINLE/Cengage Learning, 2015)
With a new component array and strong digital support, the new edition of Close up has been fully updated to be in line with the new First for Schools 2015 specifications. Close up is still as interesting, topical and up to date as ever with spectacular National Geographic photography and facts that have been carefully selected to appeal to the inquisitive minds of young teenagers